A reappraisal of routine marrow examination therapy of acute lymphoblasticv leukaemia. Issue 5 (May 1981) - Watson, D K; Robinson, A E; Bailey, C C
Abstract : Out of 557 routine marrow examinations performed in children receiving maintenance therapy, or having completed therapy, for acute lymphoblastic leukaemia or non-Hodgkin's lymphoma, only 9 marrow relapses were found. Out of 14 marrow examinations performed because of haematological or clinical indications of possible relapse, only 3 failed to confirm relapse. It is suggested that routine marrow examination to detect relapse is not worthwhile and should be stopped.